2022
DOI: 10.51253/pafmj.v72isuppl-2.3865
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis in Neurological Disorders: Frequency and Type of Adverse Effects Associated with this Procedure in Atertiary Care Hospital in Pakistan

Abstract: Objective: To determine the frequency and type of adverse effects associated with plasmapheresis among the patients with neurological disorders at a tertiary care hospital in Pakistan. Study Design: Prospective longitudinal study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Jun 2019. Methodology: The sample population comprised 150 patients with various neurological disorders requiring plasmapheresis at a tertiary care hospital in Rawalpindi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In spite of their lack of resources and experience, developing nations have been employing it successfully. 8 Mazahir et al reported that most of the indications were renal diseases. The difference in indications of TPE is likely due to difference in each centers’ specific subspecialties, center-specific patient selection criteria and classifications.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of their lack of resources and experience, developing nations have been employing it successfully. 8 Mazahir et al reported that most of the indications were renal diseases. The difference in indications of TPE is likely due to difference in each centers’ specific subspecialties, center-specific patient selection criteria and classifications.…”
Section: Discussionmentioning
confidence: 99%